Preceptor Support in Hospital Transition to Practice Programs. (December 2015) - Blegen, Mary A.; Spector, Nancy; Ulrich, Beth T.; Lynn, Mary R.; Barnsteiner, Jane; Silvestre, Josephine
Abstract : Objective: The aim of this study was to describe newly licensed RN (NLRN) preceptorships and the effects on competency and retention. Background: Preceptors are widely used, but little is known about the benefit from the perspective of the NLRN or about the models of the relationships. The National Council of State Boards of Nursing added questions about the preceptor experience in a study of transition-to-practice programs. Methods: Hospitals were coded as having high or low preceptor support in regard to scheduling NLRN on the same shifts as their preceptors, assignment sharing, and preceptor release time and a low number of preceptors per preceptee. Results: Half of the 82 hospitals were classified as high, and half as low preceptor support. NLRNs and their preceptors in high-support hospitals evaluated the preceptor experience and NLRN competence higher. In addition, NLRN retention was higher in the high-support hospitals. Conclusions: To improve NLRN competence and retention, preceptors should have adequate time with each NLRN, share shift and patient assignments, and have few preceptees assigned to each preceptor concurrently.